GAME BELAJAR BAHASA JERMAN LUVLINGUA SEBAGAI MEDIA PEMBELAJARAN BAHASA JERMAN KETERAMPILAN MENYIMAK PESERTA DIDIK SMA KELAS XI - NADHIFA, NUR AINI; Pujosusanto, Ari (LATERNE, 2021)
Currently the development of technology in various sectors is growing rapidly, one of which is the world of education. Especially during the current Covid-19 pandemic which requires learning activities from home by utilizing existing technology. Lots of applications are created to help the learning process, as well as in learning German. One of the educational applications to help the German learning process is the German learning game Luvlingua. This application can help educators to convey material and make it easier for students to learn German because this application has different features from other applications with different learning styles. However, one thing can be said as a learning medium if it meets certain requirements or components. This agrees with Azhar (2011) which states that learning media is a tool in the learning process both inside and outside the classroom, including components of learning resources or physical vehicles that contain instructional material in the student environment that can stimulate students to learn. To find out whether this application can be said to be a learning medium, the problem formulation in this scientific article is whether the LuvLingua German learning game is in accordance with the terms and conditions of learning media in learning German listening skills for class XI. German Luv Lingua as a medium for learning German listening skills for class XI. This scientific article is prepared by examining several theories and using a qualitative approach to the type of literature study. The literature review used is the theory of learning media, listening skills, the LuvLingua German learning game, and the 2013 curriculum.The results of the analysis show that there are 3 LuvLingua German learning games according to listening skills and in accordance with most of the criteria and requirements for learning media and can be used. in learning German listening skills both at the beginning and at the end of the lesson.